2016
DOI: 10.1021/acschemneuro.6b00142
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Dynamics during Continuous Intracranial Self-Stimulation: Effect of Waveform on Fast-Scan Cyclic Voltammetry Data

Abstract: The neurotransmitter dopamine is heavily implicated in intracranial self-stimulation (ICSS). Many drugs of abuse that affect ICSS behavior target the dopaminergic system, and optogenetic activation of dopamine neurons is sufficient to support self-stimulation. However, the patterns of phasic dopamine release during ICSS remain unclear. Early ICSS studies using fast-scan cyclic voltammetry (FSCV) rarely observed phasic dopamine release, which led to the surprising conclusion that it is dissociated from ICSS. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 51 publications
0
23
0
1
Order By: Relevance
“… 91 , 94 Alternatively, reference electrodes can be implanted on the day of recordings through a guide cannula. 46 , 95 , 96 …”
Section: Experimental Considerationsmentioning
confidence: 99%
“… 91 , 94 Alternatively, reference electrodes can be implanted on the day of recordings through a guide cannula. 46 , 95 , 96 …”
Section: Experimental Considerationsmentioning
confidence: 99%
“…34,37 The first ranked component captures the maximum variance inherent to the training set; and subsequent components describe the remaining variance, in a manner such that all PCs are orthogonal to another. 37,52 Then, concentration dynamics for the targeted species can be predicted in unknown data by projecting the data onto the PCs to extrapolate the contribution of each analyte contained in the training set. This approach can be very effective; however, it struggles when two analytical signals have similar sources of variance (voltammetric features).…”
Section: Fscv: Under Construction…mentioning
confidence: 99%
“…Principal component analysis is considered to be an unsupervised dimensionality reduction technique, because it creates PCs to describe variance in the predictor variables without considering the response. 52,55 By contrast, PLS regression analysis is a supervised dimensionality reduction technique that projects both the predictor and response variables onto a new vector space to find components that maximize the covariance of the projected structures. 55,56 This ‘supervision’ generally allows PLS regression models to describe the training data more efficiently with fewer components.…”
Section: Fscv: Under Construction…mentioning
confidence: 99%
“…Early studies using the traditional dopamine waveform found that phasic dopamine release disappeared during the continuous ICSS. Newer studies with an improved waveform coupled with principal component regression reevaluated the original finding and showed that while phasic dopamine release is not required to maintain ICSS behavior, small amounts of dopamine were still released (28). Numerous studies measured cue-evoked dopamine release in response to natural rewards or alcohol, using an audio or visual cue to predict the reward.…”
Section: Dopamine Measurementsmentioning
confidence: 99%